Strong association between adolescent obesity and consumption of macrolides in Europe and the USA: An ecological study - Chris Kenyon; Jolein Laumen; Sheeba S. Manoharan-Basil; Jozefien Buyze (Elsevier, 2020)
Background: The reasons underpinning the large variations in the prevalence of childhood obesity are inadequately understood. Individual level studies have found that macrolide consumption at a young age increases the risk of subsequent obesity. We hypothesized that differences in population level consumption of macrolides may explain part of the variation in the prevalence of childhood obesity. Methods: Mixed effects beta regression was used to assess the association between the prevalence of childhood obesity in countries in Europe/ states in the United States and population level consumption of macrolides and total antibiotics. Different time lags between consumption and obesity measurement were used. Results: We found that in both the USA and Europe, population level consumption of macrolides was positively associated with subsequent childhood obesity prevalence. According to our model, the observed differences in population-level macrolide consumption in Europe/USA would translate into a 13%/72% higher odds of childhood obesity 5 years later. The association held regardless of the lag period used between exposure and outcome. The association with total antibiotic consumption was more equivocal. Conclusions: Reducing macrolide consumption to that of low consumption countries may result in considerable reductions in childhood obesity.